Estratégias de reprodução do campesinato nas propriedades adquiridas a partir do programa nacional de crédito fundiário no município de Crato-CE - Silva, Hilda Maria Daniel da (2023)
The two sole National Land Reform Plans devised in Brazil throughout its history were not efficiently implemented. Historically, what occurred in Brazil was the sidelining of this crucial public policy for the socio-economic development of its population. Conversely, since the 1990s, there has been an expansion in investments in land purchase and sale programs. These policies, conceived by the World Bank, theoretically should complement land reform. However, they have been progressively territorializing in Brazil, representing one facet of counter-land reform. One such program is the National Land Credit Program (PNCF), established in 2003. In the state of Ceará, up to the present, it has been responsible for acquiring 391 properties across 116 municipalities. Guided by historical-dialectical materialism and anchored in themes and concepts of peasantry, land reform, and counter-land reform, our study aimed to comprehend how peasants on properties acquired through the National Land Credit Program are developing their productive strategies. Focusing on three properties in the municipality of Crato, Ceará—namely, São Silvestre Farm, Rural Condominium Sítio Jenipapo, and Alegre Frutas—we delimited our theme. Our temporal scope spans from 1996, the year the first land purchase and sale program was initiated in Ceará, to 2022, the period during which our data collection took place. Built on the review of literature on the subject, data obtained from the Agrarian Development Secretariat of the state of Ceará, the Agrarian Development Institute of Ceará, and data collected from peasants through semi-structured interviews, the findings presented in this study demonstrate that peasants do not possess optimal productive conditions within properties acquired through land credit. These properties face serious physical-structural limitations exacerbated by the absence of technical assistance, resulting in the peasants' diminished capacity to carry out agricultural production and compelling them to seek diverse strategies for income generation, such as selling portions of the plots. We believe this work serves as a valuable tool for a deeper understanding of the agrarian space in Ceará and provides insights for expanding discussions on the influence of international organizations on the formulation of public policies and the limitations faced by the peasantry for their reproduction on properties acquired through land purchase and sale programs.